Tumor Necrosis Factor-Like Weak Inducer of Apoptosis (TWEAK)/Fibroblast Growth Factor-Inducible 14 (Fn14) Axis in Cardiovascular Diseases: Progress and Challenges - Nerea Méndez-Barbero (Cells, 2020)
Cardiovascular diseases (CVD) are the leading cause of mortality in Western countries. CVD include several pathologies, such as coronary artery disease, stroke, peripheral artery disease, and aortic aneurysm, among others. All of them are characterized by a pathological vascular remodeling in which inflammation plays a key role. Interaction between different members of the tumor necrosis factor superfamily and their cognate receptors induce several biological actions that may participate in CVD. The cytokine tumor necrosis factor-like weak inducer of apoptosis (TWEAK) and its functional receptor, fibroblast growth factor-inducible 14 (Fn14), are abundantly expressed during pathological cardiovascular remodeling. The TWEAK/Fn14 axis controls a variety of cellular functions, such as proliferation, differentiation, and apoptosis, and has several biological functions, such as inflammation and fibrosis that are linked to CVD. It has been demonstrated that persistent TWEAK/Fn14 activation is involved in both vessel and heart remodeling associated with acute and chronic CVD. In this review, we summarized the role of the TWEAK/Fn14 axis during pathological cardiovascular remodeling, highlighting the cellular components and the signaling pathways that are involved in these processes.